Complexity in nominal plural allomorphy. A contrastive survey of ten Germanic languages - Dammel, Antje; Kürschner, Sebastian (Language complexity: Typology, contact, change., 2008)
We investigate the complexity of nominal plural allomorphy in ten Germanic languages from a contrastive and diachronic perspective. Focusing on one language family allows us to develop multidimensional criteria to measure morphological complexity and to compare different diachronical drifts. We introduce a three-step complexity metric, involving (1) a quantitative step, (2) a qualitative step, and (3) a validation step comparing the results from step (1) and (2) to actual language use. In this article, we apply the method’s two first steps to the plural allomorphy of our sample languages. Our criteria include for (1) the number of allomorphs and for (2) iconicity in form-meaning relationship, the basis of allomorph assignment, and the direction of determination between stem and suffix. Our approach reveals Faroese as the most complex language and English as the simplest one.
UnivIS-Import:2015-04-16:Pub.2008.phil.dgeko.LGDSM.comple
Keywords: Germanic languages; morphology; Faroese; English